Analysis of the Influence of Employment, Manufacturing Industry Sector on Industrial Agglomeration in Sumbagsel in Islamic Economic - Al Wasi, Raihansyah; Zulaikah, Zulaikah; Selvina, Mia (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The manufacturing industry in South Sumatra is experiencing rapid growth driven by investment, rising domestic demand, and supportive government policies, yet it also faces challenges such as globalization and supply chain disruptions. This study applies a quantitative method with panel data regression to analyze the impact of population, the Human Development Index (HDI), and trade openness on industrial agglomeration. The results indicate that while employment shows a positive but statistically insignificant effect, and the manufacturing sector a negative but also insignificant effect on industrial agglomeration, both variables collectively have a significant influence. From an Islamic economics perspective, the industry should be managed based on sharia principles, focusing on collective welfare and promoting cooperation over competition. In conclusion, although labor absorption and the manufacturing sector do not individually exert a significant effect, their combined influence plays an important role in shaping industrial agglomeration.